The Development Strategy of Buddhist Method for Happiness Society for the Elderly People, Roi Et Province - (Suphachai Butraket), Phramaha Suphachai Suphakicco; Kongsumruay, Khamphiraphap; Nahuanil , Chuleeporn; Supa, Naipraporn (Dhammathas Academic Journal, 2024)
The purposes of this research were 1) The Development Strategy of Buddhist Method for Happiness Society for the Elderly People, Roi Et Province, and 2) evaluate this strategy. The sample group for this study consisted of elderly individuals from the Mueang district of Roi Et province. This was a mixed method research. The researcher specifically chose a sample group consisting of seniors who face health-related issues, lifestyle challenges, and family-related problems. A total of 358 individuals were chosen. Data was collected through structured interviews from 9 respondents and evaluated by 17 qualified individuals. The research tools used included structured interviews, a questionnaire regarding problem conditions with 20 items. The statistics used for data analysis included frequency, percentage, mean, standard deviation, Pearson Product Moment Correlation (r), Multiple Regression Analysis (MR), and Descriptive Analysis. The research results was found that: 1. The study on the condition, problems, and factors influencing the development strategy of Buddhist method for happiness society for the elderly people, Roi Et found that the age and gender of the elderly in Roi Et predict the factors affecting the development of the Buddhist approach for an ideal society significantly (P-value = .000). These two variables explain the variance in factors affecting the development by 0.48 percent (R2 = .048). The forecast equation can be written in raw scores as: Y = 3.648 + -.054X1 + -.050X2. 2. The evaluation of the strategy for the Buddhist method for happiness society for the elderly people, Roi Et province is generally at a high level. The aspect with the highest opinions is appropriateness, followed by accuracy and feasibility. The aspect with the least opinions is practicality.